(untitled) (Journal of Information Technology and Digital World, 2020)
Presently 21st century is the world of Internet, broadband, satellite TV, mobile phone etc fueled by upcoming 5G (5th Generation) networks. We cannot live one day without internet. More than 70% of us access the Internet on a daily basis which clearly shows the huge potential of this global system of interconnected network and how people around the world get easily addicted to it. Large E- Business and E- Marketing are the outcome of the Internet invasion in human life. But do we really care or think what effect the Internet has on our environment? The reality says in coming years with massive population around 2.5 billion people will be connected to the Internet worldwide, making Internet's energy and carbon footprint will surpass air travel. Hence Internet does not look as green as thought but responsible for Carbon dioxide (CO2) emissions from Cloud Storage, use of various search engines and Emails. This article highlights some adverse effect of Internet on planet Earth and environment as well. Some possible remedies are also discussed for cut in our possible online carbon footprint.